EFFECT OF COLLIMATOR ELEMENTS ON THE BEAM SPECTRUM AND KERMA IN GAMMA IRRADIATOR - Rasito Tursinah; Bunawas Bunawas; Tri Cahyo; Ade Suherman; P Sukmabuana (Website, 2021)
In the development of low-medium energy photon calibration facilities we have simulated several types of gamma irradiator collimator materials with ISO 4037-1 design connected to the output beam spectrum and the resulting kerma. Four types of collimator material, namely Al, Fe, Pb, and WCu have been simulated with gamma radiation sources 241Am, 57Co, 137Cs, and 60Co. Simulations were carried out using the Monte Carlo method with the PHITS computer program. Based on the comparison of air kerma produced, collimators made from Al are suitable for gamma sources 241Am, Fe material for gamma sources 57Co, and Pb material for sources 137Cs and 60Co.